2021
DOI: 10.1002/pen.25750
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of tensile strength with crosslink density for the high‐carbon black‐filledEPDMcompounds with various softeners

Abstract: Equilibrium swelling and rheological tests were adopted to systematically investigate the effects of softener type and dosage on the crosslink densities. The results turned out that the chemical crosslink density could be distinguished from the physical crosslink density by comparing the results of equilibrium swelling and rheological tests. The liquid butadiene (LB) as a softener leads to the greatest reduction in crosslink density, followed by polyethylene wax (PW) and paraffinic oil (PO). The tensile streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…We observed that the thermoset containing a 5% TK-1 cross-linker was more elastic than the ones with 10 and 20% cross-linkers due to the decreased cross-linking density (Figure B). Chemical cross-linkers can produce a 3D network inside a polymer structure, increasing the hardness and tensile strength . Thus, we observed that the thermoset poly­(HEA), containing 20% TK-1, had a higher tensile strength than the samples containing only 10 and 5% TK-1 (Figure C).…”
Section: Results and Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…We observed that the thermoset containing a 5% TK-1 cross-linker was more elastic than the ones with 10 and 20% cross-linkers due to the decreased cross-linking density (Figure B). Chemical cross-linkers can produce a 3D network inside a polymer structure, increasing the hardness and tensile strength . Thus, we observed that the thermoset poly­(HEA), containing 20% TK-1, had a higher tensile strength than the samples containing only 10 and 5% TK-1 (Figure C).…”
Section: Results and Discussionmentioning
confidence: 76%
“…Chemical cross-linkers can produce a 3D network inside a polymer structure, increasing the hardness and tensile strength. 30 Thus, we observed that the thermoset poly(HEA), containing 20% TK-1, had a higher tensile strength than the samples containing only 10 and 5% TK-1 (Figure 2C). Cleavage of the thioketal moiety with a specific ratio significantly affects the alteration of the mechanical and rheological properties of TK-poly(HEA).…”
Section: Investigation Of the Degradation And The Mechanical Properti...mentioning
confidence: 75%
“…The cross-linking density was determined using the equilibrium swelling method. [19] The samples were swollen in toluene at room temperature for 72 h and thereafter removed from the solvent and the surface toluene was blotted off quickly using tissue paper. The samples were immediately weighed on an analytical balance and further dried in a vacuum oven for 36 h at 80 C to remove all the solvent and reweighed.…”
Section: Swelling Testmentioning
confidence: 99%
“…[17,18] The in-situ reaction in rubber could improve the tensile strength, tear strength, modulus, and maintain a superior elongation at break. In addition to ZDMA, magnesium dimethacrylate can be applied to reinforce various types of rubber, such as NR, Styrene Butadiene Rubber (SBR), NBR, EPDM, and ethylene-vinyl acetate copolymer, [19][20][21][22][23][24] and it can enhance the tensile strength and improve the elastic modulus of rubber.…”
mentioning
confidence: 99%
“…It can be seen from Figure4A, ν e decreases first and then increases with increasing NR content, and reaches the minimum value at the NR content of 60%. It is because that the different reactivities of NR and CIIR to sulfur results in the failure of covulcanization of the compound, that is, rarely co-crosslinking between the two phases of the rubber blends is formed 18. F I G U R E 3 The effect of raw rubber ratio on the vulcanization characteristics of the rubber blends.…”
mentioning
confidence: 99%